Teaching Lessons From COVID-19: One Department’s Story of Transformation -- An HBCU Narrative (International Journal of Multidisciplinary Perspectives in Higher Education, 2020)
When the coronavirus pandemic hit the nation, colleges and universities in Maryland canceled face-to-face classes and switched to teaching their courses online in mid-March. The following exploratory study examines how the Department of Strategic Communication at Morgan State University (MSU), the largest historically Black university in the state, adapted aspects of its existing departmental culture in order to pivot to an emergency remote teaching environment during the coronavirus crisis. Through the lived-experience narratives of students, faculty, and staff, this study adds to the conversation about the value of compassionate teaching, community-building, co-creative learning, and course structuration. The article offers reflexive strategies and lessons for developing digital approaches to learning for the present and for crisis situations as a sustainable model.